2000
DOI: 10.1074/jbc.m006513200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Enzymatic Properties of the Yeast Dna2 Helicase/Endonuclease Suggests a New Model for Okazaki Fragment Processing

Abstract: The Saccharomyces cerevisiae Dna2, which contains single-stranded DNA-specific endonuclease activity, interacts genetically and physically with Fen-1, a structure-specific endonuclease implicated in Okazaki fragment maturation during lagging strand synthesis. In this report, we investigated the properties of the Dna2 helicase/endonuclease activities in search of their in vivo physiological functions in eukaryotes. We found that the Dna2 helicase activity translocates in the 5 to 3 direction and uses DNA with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
266
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(283 citation statements)
references
References 53 publications
14
266
3
Order By: Relevance
“…The preparation of substrates and their labeling at either 5Ј-or 3Ј-end were as described previously (2,15). The structure and position of radioisotopic labels (indicated by asterisks) in substrates are described in each figure.…”
Section: Oligonucleotides and Preparation Of Helicase And Nucleasementioning
confidence: 99%
See 2 more Smart Citations
“…The preparation of substrates and their labeling at either 5Ј-or 3Ј-end were as described previously (2,15). The structure and position of radioisotopic labels (indicated by asterisks) in substrates are described in each figure.…”
Section: Oligonucleotides and Preparation Of Helicase And Nucleasementioning
confidence: 99%
“…Reactions were carried out at 37°C for 5 min unless indicated otherwise. The products were boiled, when necessary, followed by separation in low resolution gels (12% polyacrylamide gel containing 0.5% SDS and 7 M urea) or high resolution denaturing gels as described previously (15). Gels were dried on DEAE-cellulose paper and subjected to autoradiography.…”
Section: Oligonucleotides and Preparation Of Helicase And Nucleasementioning
confidence: 99%
See 1 more Smart Citation
“…RAD27, the homolog of the mammalian FEN-1, is a structure-specific nuclease implicated in Okazaki fragment maturation during DNA replication. These genetic interactions suggested that at least one specific role for Dna2p is also in the maturation of the 5Ј ends of Okazaki fragments (Budd and Campbell, 1997), and in vitro reconstitution studies indicate that Dna2 is required for efficient RNA removal and ligation when FEN-1 activity is impaired (Bae and Seo, 2000;Ayyagari et al, 2003; Kao, Campbell, and Bambara, unpublished data). With respect to aging, it is interesting that the human BLM gene, encoding a RecQ helicase defective in Bloom syndrome, can suppress the replication defect of dna2 mutants (Imamura and Campbell, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…FEN-1 is highly conserved between yeast and human, and is a 5' flap specific endonuclease (Li et al, 1995). The 5'-flap structure can occur by strand displacement at 5' ends of Okazaki fragments during lagging strand synthesis, and can be removed by FEN-1 and other replication proteins, resulting in nicked double strand DNA suitable for ligation (Gordenin et al, 1997;Bae and Seo, 2000). On primertemplate substrates containing a flap structure, FEN1 employs unknown mechanism to cleave the 5'-tail.…”
Section: Introductionmentioning
confidence: 99%